Australian Social Work Research: An Empirical Study of Engagement and Impact. (3rd December 2020) - Tilbury, Clare; Bigby, Christine; Fisher, Mike; Hughes, Mark
Abstract: Internationally, non-academic research impact is assessed by governments as part of evaluating the quality of publicly funded research. A case study method was used to investigate the non-academic impact of Australian social work research. Interviews were conducted with fifteen leading researchers about outputs (research products, such as publications and reports), engagement (interaction between researchers and end-users outside academia to transfer knowledge, methods or resources) and impact (social or economic contributions of research). Twelve case studies were prepared using a standardised template. Content analysis highlighted examples of impact, and theoretical and in vivo coding uncovered processes of engagement and impact. Different types of engagements with research end-users influenced impact in three areas: legislation and policy; practices and service delivery; and quality of life of community members. Engagement and impact were intertwined as research altered policy discourses and illuminated hidden social issues, preparing ground for subsequent, more direct impact. Likewise, academic and non-academic impacts were intertwined as research rigour and academic credibility were perceived to leverage influence. There was no evidence of achieving impact simply through the trickle-down effect of scholarly publication. The findings broaden understandings of how research influences policy and practice and iterative and indirect relationships between engagement and impact.